Toward Semantics-Based answer pinpointing - Hovy, Eduard; Gerber, Laurie; Hermjakob, Ulf; Lin, Chin-Yew; Ravichandran, Deepak (The First International Conference on Human Language Technology Research (HLT'01), 2001)
We describe the treatment of questions (Question-Answer Typology, question parsing, and results) in the Weblcopedia question answering system.